Treatment of edible oil refinery wastewater. - Chin, K.K.; Wong, K.K.
Edible oil refinery wastewater containing high concentration levels of organics and solids were treated by physical-chemical and biological processes. Physical-chemical treatment alone would not produce on effluent that met with the Malaysian effluent standards. Activated sludge treatment followed with chemical coagulation and flocculation brought the BOD level down to 50mg/l. The COD level remained above 200mg/l ,and colour was higher than 600 Hazen units. Chemical oxidation with up to 50mg/l sodium hypochloride brought chemical treatments system is provided for comparison.